1996
DOI: 10.1093/carcin/17.9.1799
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability differences between familial and sporadic ovarian cancers

Abstract: DNA instability, reflected in altered patterns of short tandem repeat sequences (microsatellites) in dividing cells, has been described in hereditary non-polyposis colon cancer (HNPCC) and in other tumor types. Ovarian cancer (OC), although most often a sporadic cancer, can recur, with HNPCC, as part of the Lynch cancer family syndrome. In an investigation of microsatellite instability (MIN) in 90 OC cases, we found MIN in 3/28 (11%) OC cases with, and 8/62 (13%) without, a family history of cancer. For 2/3 MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 23 publications
3
40
0
Order By: Relevance
“…We demonstrated that hMSH2 protein is exclusively localized in the nuclear compartment and is expressed in the vast majority of neoplastic cells from primary ovarian tumours. These results are consistent with those of Brown et al (1997), and with previous demonstrations that microsatellite instability occurs with a low prevalence in advanced stage ovarian cancer (King et al, 1995;Arzimanoglou et al, 1996), indicating that the majority of tumour cells from these patients carry a functional hMSH2 genes. Western blotting analysis revealed that hMSH2 and GTBP display a wide range of expression levels, suggesting that both these proteins could play a role in the biology of ovarian tumour cells.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated that hMSH2 protein is exclusively localized in the nuclear compartment and is expressed in the vast majority of neoplastic cells from primary ovarian tumours. These results are consistent with those of Brown et al (1997), and with previous demonstrations that microsatellite instability occurs with a low prevalence in advanced stage ovarian cancer (King et al, 1995;Arzimanoglou et al, 1996), indicating that the majority of tumour cells from these patients carry a functional hMSH2 genes. Western blotting analysis revealed that hMSH2 and GTBP display a wide range of expression levels, suggesting that both these proteins could play a role in the biology of ovarian tumour cells.…”
Section: Discussionsupporting
confidence: 92%
“…Instability at widespread highly polymorphic tandem repeat DNA sequences, known as microsatellites, has been reported in hereditary nonpolyposis colorectal cancer (HNPCC; Thibodeau et al, 1993), as well as in a number of other familial and sporadic cancers including colon (Ionov et al, 1993), endometrium (Duggan et al, 1994), oesophagus , stomach (Rhyu et al, 1994), pancreas (Brentnall et al, 1995), lung (Shridhar et al, 1994;Merlo et al, 1994), bladder (Gonzalez-Zulueta et al, 1993), kidney , breast (Paulson et al, 1996), ovary (Arzimanoglou et al, 1996), brain (Zhu et al, 1996) and haematopoietic system Kaneka et al, 1996), and some preneoplastic or in¯ammatory tissues (Brentnall et al, 1995(Brentnall et al, , 1996Salvucci et al, 1996). In sporadic tumours, the extension and the type of microsatellite alterations is generally less pronounced than in HNPCC patients and often appears as one or few additional alleles at only one or few loci (Wooster et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In primary epithelial ovarian cancer, the percentage of tumours positive for MSI has been reported to be no more than 12% (Arzimanoglou et al, 1996) to 26% (Codegoni et al, 1999), and even in ovarian cancers without MSI, it is uncommon to experience little or no tumour reduction with CDDP treatment. Therefore, it is difficult to predict a tumour's resistance to CDDP solely by the presence or absence of MSI in the primary tumour.…”
Section: Discussionmentioning
confidence: 99%